2008
DOI: 10.1002/ange.200704687
|View full text |Cite
|
Sign up to set email alerts
|

Allylation of Ketones with a Ferrocene‐Based Planar Chiral Lewis Acid

Abstract: Flach wie eine Hand: Die Enantiomere der zweizähnigen Lewis‐Säure 1,2‐Fc(BMeCl)(SnMe2Cl) können durch stereoselektive Komplexierung mit N‐Methylpseudoephedrin leicht getrennt werden. Die resultierenden planar‐chiralen Lewis‐Säuren, deren optische Reinheiten 97 % übersteigen, können nach Umwandlung in die abgebildeten Allylboranderivate schnell und mit Enantioselektivitäten bis 80 % an Ketone addieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Keywords: boron · chirality · ferrocenes · ferrocenylboranes · Lewis acids A C H T U N G T R E N N U N G (BClMe)A C H T U N G T R E N N U N G (SnMe 2 Cl) (A, Fc= ferrocene) can be resolved into its constituent planar chiral enantiomers and that these can be subsequently employed in the enantioselective allylation of ketones. [20] In this context, we would like to also note that Aldridge and co-workers recently obtained compound B in enantiomerically pure form by regioselective ortho-metalation and subsequent diastereomer separation by recrystallization (see Scheme 1). [21] Herein, we describe a high-yielding enantioselective synthesis route to the planar chiral napththyl ferrocenylborane 1,2-Fc(Np)A C H T U N G T R E N N U N G (BCl 2 ) (Np= naphthyl), which in turn serves as a versatile precursor to other chiral organoborane Lewis acids through subsequent transmetalation reactions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Keywords: boron · chirality · ferrocenes · ferrocenylboranes · Lewis acids A C H T U N G T R E N N U N G (BClMe)A C H T U N G T R E N N U N G (SnMe 2 Cl) (A, Fc= ferrocene) can be resolved into its constituent planar chiral enantiomers and that these can be subsequently employed in the enantioselective allylation of ketones. [20] In this context, we would like to also note that Aldridge and co-workers recently obtained compound B in enantiomerically pure form by regioselective ortho-metalation and subsequent diastereomer separation by recrystallization (see Scheme 1). [21] Herein, we describe a high-yielding enantioselective synthesis route to the planar chiral napththyl ferrocenylborane 1,2-Fc(Np)A C H T U N G T R E N N U N G (BCl 2 ) (Np= naphthyl), which in turn serves as a versatile precursor to other chiral organoborane Lewis acids through subsequent transmetalation reactions.…”
Section: Introductionmentioning
confidence: 96%
“…19 Prior efforts by our group involved studies on the binding properties of heteronuclear bidentate 1‐stannyl‐2‐borylferrocene derivatives, which are obtained in their racemic form by a rearrangement reaction from 1,1′‐bis(trimethylstannyl) ferrocene and boron halides RBCl 2 (R=Cl, Ph, C 6 F 5 ) 13. 14 We have demonstrated that the bidentate Lewis acid 1,2‐Fc(BClMe)(SnMe 2 Cl) ( A , Fc=ferrocene) can be resolved into its constituent planar chiral enantiomers and that these can be subsequently employed in the enantioselective allylation of ketones 20. In this context, we would like to also note that Aldridge and co‐workers recently obtained compound B in enantiomerically pure form by regioselective ortho ‐metalation and subsequent diastereomer separation by recrystallization (see Scheme ) 21…”
Section: Introductionmentioning
confidence: 99%